T cell epitope content comparison using EpiCC correlates with vaccine efficacy against heterologous porcine reproductive and respiratory syndrome virus type 2 strains - J. Mark Hammer; Andres H. Gutierrez; Lucas Huntimer; Benjamin Gabriel; William D. Martin; Sabine E. Hammer; Tobias Käser; Anne S. De Groot (Frontiers in Microbiology)
Porcine reproductive and respiratory syndrome virus (PRRSV) is one of the most ubiquitous RNA viruses affecting pigs and pig farms globally. While vaccines are available, they are not entirely effective, and the introduction of modified live virus vaccines (MLV) has contributed to an increase in the rate of viral evolution. While vaccines induce humoral responses that may contribute to immunity against PRRSV, vaccines containing T cell epitopes that are well-matched to circulating strains are believed to be more likely to induce protective effects upon challenge or field exposure. We developed an algorithm that performs T cell epitope content comparison (EpiCC) based on PRRSV sequence data, that may assist veterinarians, practitioners, producers, and farmers to select and design well-matched vaccines for use against circulating PRRSV isolates. A recently published vaccination-challenge experiment provided an opportunity to test EpiCC. We hypothesized that higher conservation of T cell epitope content between the MLV vaccine and challenge viruses would be associated with better protective effects of vaccination. We used the EpiCC algorithm to compare the T cell epitope content contained in the MLV Prevacent® vaccine used in the study and four heterologous type 2 (PRRSV-2) challenge strains. In this comparison, higher EpiCC coverage scores correlated not only with higher T cell responses observed in the efficacy study but also with better protection. The results also indicate that while genotyping may currently depend on GP5 analysis, it is unlikely that the genotyping performed using GP5 will be closely associated with protective relationships between vaccines and lineages. This suggests T cell epitope analysis of existing and new vaccines for epitope coverage may improve vaccine selection for an economically important porcine virus; it also points to the need to measure and thus improve T cell epitope content in PRRSV vaccines to maximize their protective efficacy against field strains.